2013
DOI: 10.1155/2013/581984
|View full text |Cite
|
Sign up to set email alerts
|

Filter Cake and Vinasse as Fertilizers Contributing to Conservation Agriculture

Abstract: Utilising organic residues in agriculture contributes to the conservation of natural resources by recycling carbon and mineral elements. Organic residues produced by the sugar and alcohol agroindustries have great potential for use in conservation agriculture. The production of sugar and alcohol generates large quantities of byproducts, such as filter cake and vinasse, which can be used as soil improvers and substitutes for inorganic phosphorus and potassium fertilizers. However, the use of these residues in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
133
1
33

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 39 publications
2
133
1
33
Order By: Relevance
“…That study noted that the application of vinasse helps in slowing the release of nutrients and organic matter, which aids in increased soil fertility and improved soil structure (Arafat & Yassen, 2002). Prado et al (2013) highlighted studies in Brazil and China that noted vinasse as an ideal organic fertilizer that can produce greater yields when the correct application rates are used. In Brazil, using vinasse in sugar cane cultivations showed increased nutrient concentrations in the fields and improved radicular systems of the sugarcane, and in China vinasse resulted generally in increased soil fertility and the presence of residual nutrients in the soil after harvesting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That study noted that the application of vinasse helps in slowing the release of nutrients and organic matter, which aids in increased soil fertility and improved soil structure (Arafat & Yassen, 2002). Prado et al (2013) highlighted studies in Brazil and China that noted vinasse as an ideal organic fertilizer that can produce greater yields when the correct application rates are used. In Brazil, using vinasse in sugar cane cultivations showed increased nutrient concentrations in the fields and improved radicular systems of the sugarcane, and in China vinasse resulted generally in increased soil fertility and the presence of residual nutrients in the soil after harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high nutrient content, vinasse is an attractive and environmentally acceptable soil amendment option for the agricultural industry. Studies in Brazil indicated that vinasse applied in appropriate volumes to sugar cane can partially or completely replace chemical fertilizers (Prado et al, 2013). With the development of the Bioethanol Plant here in Guyana, copious amounts of vinasse are being produced and it is crucial that an economic return be sought from this effluent.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale vinasse applications are an effective economic alternative for sugar cane irrigation and fertilisation given their high levels of potassium, calcium and organic matter in the chemical composition, as well as moderate amounts of nitrogen and other nutrients (Prado et al, 2013). However, such applications have been reported to confer both benefits and demerits for soil quality, water and sugar cane production in field trial research, and in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 different agroclimatic regions (Da Silva et al, 2007;Prado et al, 2013;Teixeira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, such applications have been reported to confer both benefits and demerits for soil quality, water and sugar cane production in field trial research, and in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 different agroclimatic regions (Da Silva et al, 2007;Prado et al, 2013;Teixeira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While vinasse has been considered as a serious environmental problem due to potential discharge into water bodies (CÓ JUNIOR; MARQUES; TASSO JÚNIOR, 2008). A recent evaluation by Prado et al (2013) highlighted that vinasse application is not necessarily an environmental problem, and can in fact be used for several benefits. Since the 1980s applying vinasse as a fertiliser became a standard practice in order to lower costs associated with chemical fertiliser (LAIME et al, 2011).…”
Section: Effects Of Vinasse Application On Soil C (Nv Vs V)mentioning
confidence: 99%